Enabling Rapid Financial Response to Disasters: Knotting and Reknotting Multiple Paradoxes in Interorganizational Systems - Jarzabkowski, Paula; Bednarek, Rebecca; Chalkias, Konstantinos; Cacciatori, Eugenia (Academy of Management Journal, 2022)
While market-based solutions are increasingly being proposed to address major societal and development issues, they are also often considered antithetical to issues such as climate change, poverty alleviation and disaster response. In particular, the interorganizational systems involved in such market solutions gives rise to multiple contradictory tensions, known as paradoxes. We therefore adopt a paradox lens to explain the dynamics through which different actors within these systems navigate the contradictions that are generated. Drawing on a global qualitative study of multi-country risk pools that provide rapid capital in the immediate aftermath of disaster, we advance paradox theory by showing how organizational actors’ interactions i) maintain equilibrium by generating mutually reinforcing balance among paradoxes, whilst ii) the clustering of poles from different paradoxes generates disequilibrium, and iii) the reknotting of poles from different paradoxes restores equilibrium. As our process framework shows, these dynamics form an iterative cycle between equilibrium and disequilibrium that is essential in enhancing the promise of market-based solutions to address development issues; in our study increasing the rapid availability of capital to respond to disasters such as hurricanes, earthquakes and droughts.